Students’ English Skills Development Through the English Time Program: Peningkatan Kemampuan Bahasa Inggris Siswa Melalui Program Waktu Bahasa Inggris - Hidayah, Rahmad; Hidayatulloh, Hidayatulloh (Universitas Muhammadiyah Sidoarjo, 2025)
Background: English is an essential skill that needs to be mastered from the elementary level to prepare students for global competition. Specific Background: However, many students in primary schools still face difficulties in listening, reading, writing, and speaking English fluently. Knowledge Gap: Few studies have explored structured school programs that integrate fun and interactive learning activities to improve students’ English proficiency. Aim: This study aims to describe the implementation of the English Time program at SD Muhammadiyah 2 Tulangan as an effort to improve students’ English language skills. Results: The findings show that four main strategies were implemented: listening exercises, reading practices, writing activities, and speaking sessions. These strategies significantly helped students become more confident and engaged in learning. Novelty: This study provides a practical example of a school-based program that successfully integrates enjoyable activities into daily routines. Implications: The results may serve as a reference for other schools to design similar programs to strengthen students’ English skills. Highlights:• English Time program improves four English skills• Students become more active and confident in learning• Program provides a replicable model for other schools Keyword: English Time, Listening, Reading, Writing, Speaking